Pemberdayaan Komunikasi Pemuka Pendapat dalam Penanganan Bencana Gempa Bumi Di Yogyakarta (Kasus Kabupaten Bantul) - M. Badri; M. Hubeis; Maksum . (Institut Pertanian Bogor, 2008)
This research is aimed at knowing communication empowerment for opinion leaders in the post-disaster handling of the Yogyakarta earthquake, especially in Bantul Regency. The analysis was held to find out the opinion leader's personal characteristics, opinion leader's communication behavior, community group, opinion leader'scommunication empowerment in the post-disaster handling and also the influence of the opinion leader's personalcharacteristics, opinion leader's communication behavior, community group, for opinion leader's communicationempowerment in the post-disaster handling of the Yogyakarta earthquake. This research was designed as surveymethods, using simple random sampling methods for 91 respondents. The analysis was done by descriptivefrequency, Chi-Square and multiple regression. The result shown that opinion leader's occupation has influence tothe basic social service in the opinion leader's communication empowerment in disaster handling. Opinion leader'ssalary has influence to the program information. Personage has influence to the basic social service. Opinionleader's responses to mass media has influence to the victim rescue stage. Community group has real influence to theempowerment disaster handling communication. Group structure occupation has strong influence to the temporaryhousing. Group building has strong influence to the reconstruction housing. Group cohesion has strong influence to all activity of the empowerment disaster handling communication. Group atmosphere has strong influence to thetemporary housing. Group pressure influence to the mental rehabilitation only. Group direction has strong influenceto the temporary housing. The communication empowerment for opinion leaders is necessary to make the postdisasterhandling program successful.